TROLLing - The Tromsø Repository of Language and Linguistics - Conzett, Philipp; Andreassen, Helene N.; Høydalsvik, Stein; Janda, Laura Alexis; Longva, Leif; Nesset, Tore; Odu, Obiajulu (2014)
Poster presentation at The 9th Munin Conference on Scholarly Publishing, Tromsø, 26.11-27.11 2014.